2021
DOI: 10.5435/jaaos-d-20-00658
|View full text |Cite
|
Sign up to set email alerts
|

One Dose Versus Two Doses of Intravenous Tranexamic Acid in Total Joint Arthroplasty

Abstract: Introduction:Despite its widespread use, a single formulation or dosing regimen of tranexamic acid (TXA) has not been universally agreed on for total joint arthroplasty. The purpose of this study is to compare previously uninvestigated single-dose and two-dose regimens in postoperative hemoglobin level and secondary outcomes within 30 days of surgery.Methods:A retrospective search of our institution's database of patients who underwent primary total knee arthroplasty and primary total hip arthroplasty between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…The initial review yielded 1238 papers [(Pubmed ( n = 239), Embase ( n = 261), Web of Science ( n = 385), Cochrane Library ( n = 22), and Medline ( n = 331)] after removing duplicates, and a total of 580 papers were screened. A total of 510 studies were excluded at the title and abstract level, and 5 studies were finally included by reading the full text and nadir criteria [ 28 , 30 , 38 40 ]. A total of 5542 patients were included for data extraction and meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial review yielded 1238 papers [(Pubmed ( n = 239), Embase ( n = 261), Web of Science ( n = 385), Cochrane Library ( n = 22), and Medline ( n = 331)] after removing duplicates, and a total of 580 papers were screened. A total of 510 studies were excluded at the title and abstract level, and 5 studies were finally included by reading the full text and nadir criteria [ 28 , 30 , 38 40 ]. A total of 5542 patients were included for data extraction and meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…3 A). Sensitivity analysis was performed and found that after excluding the Charette 2019 and Golz 2021gramroups of trials [ 39 , 40 ], although the point estimates were in the same direction; the results of the remaining three groups still showed no difference between the two groups, but heterogeneity I 2 from 80 to 36% (RD = 0.00, 95% CI [− 0.01, 0.02], P = 0.32, Fig. 3 B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our approach involved a single adequately dosed shot to inhibit fibrinolysis during peak blood loss, without the need for repeated doses. Multiple trials have confirmed the efficacy of single-shot TXA compared to repeated-dose regimens [ 14 , 25 , 26 ]. The use of TXA plays a positive role in primary TKA, reducing the occurrence of hematomas [ 27 ], hidden blood loss, and the need for allogeneic blood transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the specific case, dosing recommendations have ranged from administering TXA at a dose of 15 mg/kg of body weight 12 to administering a bolus ranging from 1 to 4 g of TXA 13,14 . Some studies have experimented with providing multiple doses of TXA but have generally found similar outcomes between single and multiple-dose groups 15 . Common contraindications include a known allergy to TXA, intracranial hemorrhage, renal dysfunction, and history of thrombosis 16,17 .…”
mentioning
confidence: 99%